Reinforced dental plaster with low setting expansion and enhanced microhardness - Hamdy, Tamer M. (2021)
The results revealed that innovative dental plaster reinforced by 10 wt.% aluminum oxide nanoparticle fillers was shown higher mean surface microhardness than that of conventional dental plaster, while higher mean compressive strength values than that of improved stones and conventional dental plaster. Moreover, reinforced dental plaster was shown lower mean setting expansion values compared with conventional dental plaster and improved stones (P value ≤ 0.05).